Problematik Pembelajaran Teks Persuasi Kelas VIII D SMP Negeri 7 Kota Jambi - Yusra, Hilman; Susanto, Fitra Edi (Universitas PGRI Semarang, 2024)
This study aims to describe the problematics of persuasion text learning. The research method used is qualitative research. The type of research used in this study is a phenomenological type of research. This study describes problematic research in writing descriptive texts for class VIII D students of SMP Negeri 7 Jambi City by using phenomenological research. From the results of research that has been carried out by researchers on class VIII D students of SMP Negeri 7 Jambi City, this research data was obtained by conducting class observations, documentation in the form of photos and student assignments in the Indonesian language learning process and distributing questionnaires to students and eye teachers. Indonesian lessons. After the data was obtained, the data were analyzed using qualitative methods using descriptive techniques. there are some problems or problems encountered. The teacher's problems are contained in the lesson plans, approaches and methods as well as task assessment. While students' problems on interest and motivation some students did not pay full attention when the teacher was explaining. This hinders the student's teaching and learning process for the next stage. At the implementation stage of writing persuasive texts, students are also faced with external constraints, namely the media applied by the teacher, students feel less like learning media. The conclusion of this research is that teachers are advised to give more specific directions to students who have problems with writing descriptive texts, so that no more students experience problems in this regard. while students should before the learning process occurs, understand in advance the material to be studied, namely about writing descriptive text so that the teaching and learning process is carried out actively.